Prevalence of and factors associated with late diagnosis of HIV in Malawi, Zambia, and Zimbabwe: Results from population-based nationally representative surveys. - Andreas D Haas; Elizabeth Radin; Sehin Birhanu; Andrea J Low; Suzue Saito; Karampreet Sachathep; Shirish Balachandra; Julius Manjengwa; Yen T Duong; Sasi Jonnalagadda; Danielle Payne; George Bello; et al. (Public Library of Science (PLoS), 2022)
Introduction Late diagnosis of HIV (LD) increases the risk of morbidity, mortality, and HIV transmission. We used nationally representative data from population-based HIV impact assessment (PHIA) surveys in Malawi, Zambia, and Zimbabwe (2015-2016) to characterize adults at risk of LD and to examine associations between LD and presumed HIV transmission to cohabiting sexual partners. Methods We estimated the prevalence of LD, defined as CD4 count <350 cells/μL, among adults newly diagnosed with HIV during the surveys and odds ratios for associated factors. We linked newly diagnosed adults (index cases) to their household sexual partners and calculated adjusted odds ratios for associations between LD of the index case, viral load of the index case, and duration of HIV exposure in the relationship, and the HIV status of the household sexual partner. Results Of 1,804 adults who were newly diagnosed with HIV in the surveys, 49% (882) were diagnosed late. LD was associated with male sex, older age, and almost five times the odds of having an HIV-positive household sexual partner (adjusted odds ratio [aOR], 4.65 [95% confidence interval: 2.56-8.45]). Longer duration of HIV exposure in a relationship and higher viral load of the index case were both independently associated with higher odds of having HIV-positive household sexual partners. Individuals with HIV exposure of more than 5 years had more than three times (aOR 3.42 [95% CI: 1.63-7.18]) higher odds of being HIV positive than those with less than 2 years HIV exposure. The odds of being HIV positive were increased in individuals who were in a relationship with an index case with a viral load of 400-3499 copies/mL (aOR 4.06 [95% CI 0.45-36.46]), 3,500-9,999 copies/mL (aOR 11.32 [95% CI: 4.08-31.39]), 10,000-49,999 copies/mL (aOR 17.07 [95% CI: 9.18-31.72]), and ≥50,000 copies/mL (aOR 28.41 [95% CI: 12.18-66.28]) compared to individuals who were in a relationship with an index case with a viral load of <400 copies/mL. Conclusions LD remains a challenge in Southern Africa and is strongly associated with presumed HIV transmission to household sexual partners. Our study underscores the need for earlier HIV diagnosis, particularly among men and older adults, and the importance of index testing.